1988
DOI: 10.1007/bf02556338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one-year treatment with estrogens on bone mass, intestinal calcium absorption, and 25-hydroxyvitamin D-1α-hydroxylase reserve in postmenopausal osteoporosis

Abstract: A double-blind, placebo-controlled study on 21 postmenopausal osteoporotic women was performed in order to assess the effects of 1 year estrogen therapy (Premarin, 1.25 mg/day) on bone mass, intestinal calcium absorption, and mineral metabolism. Bone mineral content (BMC), measured by dual photon absorptiometry on the vertebral bodies and the femoral shaft, increased in both areas, but the changes were more evident at the former site, which is predominantly trabecular (+8.3%, P less than 0.05), than at the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(70 citation statements)
references
References 61 publications
7
61
1
1
Order By: Relevance
“…With the use of cultured opossum kidney cells, a suppressive effect of 17␤-E 2 on 1␣-OHase activity was demonstrated (33). Among postmenopausal women, however, estrogen replacement therapy resulted in unchanged or increased renal 1␣-OHase activity (30,34 (20,29,36,37). In contrast, some studies suggested a direct effect of 17␤-E 2 on Ca 2ϩ reabsorption, independent of vitamin D (3,28).…”
Section: Discussionmentioning
confidence: 99%
“…With the use of cultured opossum kidney cells, a suppressive effect of 17␤-E 2 on 1␣-OHase activity was demonstrated (33). Among postmenopausal women, however, estrogen replacement therapy resulted in unchanged or increased renal 1␣-OHase activity (30,34 (20,29,36,37). In contrast, some studies suggested a direct effect of 17␤-E 2 on Ca 2ϩ reabsorption, independent of vitamin D (3,28).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, available data indicate that decreased basal levels of 1,25(OH) 2 D 3 cannot solely account for the decrease in calcium absorption (Francis et al 1984), suggesting that the intestines of estrogen-depleted elderly or ovariectomized women are resistant to 1,25(OH) 2 D 3 (Gennari et al 1990). In addition, E2 administration has been shown to effectively restore the normal responsiveness of the intestine to 1,25(OH) 2 D 3 in ovariectomized pre- (Gennari et al 1990) and postmenopausal (Civitelli et al 1988, Heaney et al 1978 women.…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol replacement also prevented intestinal tumorigenesis and ameliorated enterocyte migration and intercellular adhesion in the Apc Min−/+ colorectal carcinoma mouse model (18). Furthermore, estrogen increases expression of VDR in rat intestine (19,20) and estrogen administration restores the responsiveness of the intestine to 1,25-dihydroxyvitamin D [1,25(OH 2 )D] in ovariectomized premenopausal (21) and postmenopausal women (22). Other tissues and cell systems, such as uterus (23), liver (24), and breast cancer cells (25), also respond to estradiol by increased VDR expression.…”
mentioning
confidence: 99%